2020
DOI: 10.3390/molecules25092217
|View full text |Cite
|
Sign up to set email alerts
|

Can We Discover Truffle’s True Identity?

Abstract: This study used elemental and stable isotope composition to characterize Slovenian truffles and used multi-variate statistical analysis to classify truffles according to species and geographical origin. Despite the fact that the Slovenian truffles shared some similar characteristics with the samples originating from other countries, differences in the element concentrations suggest that respective truffle species may respond selectively to nutrients from a certain soil type under environmental and soil conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 82 publications
(173 reference statements)
0
14
0
2
Order By: Relevance
“…Dots on the vertical lines refer to the results obtained from the literature, whereas lines indicate the span of values. The 87 Sr/ 86 Sr isotope ratios in Slovenian truffles are also presented [39].…”
Section: Strontium Isotope Ratio Of Authentic Slovenian Milkmentioning
confidence: 99%
“…Dots on the vertical lines refer to the results obtained from the literature, whereas lines indicate the span of values. The 87 Sr/ 86 Sr isotope ratios in Slovenian truffles are also presented [39].…”
Section: Strontium Isotope Ratio Of Authentic Slovenian Milkmentioning
confidence: 99%
“…This special issue also includes several papers that use stable isotope ratios, elemental profiles, and fatty acid composition to assure the authenticity and origin of high-quality products typical of the national identities of Mediterranean countries such as Moroccan argan oil [ 8 ], Portuguese meat products from Iberian black pigs [ 9 ], and Slovenian truffles [ 10 ]. These studies form part of the REALMed project “Pursuing authenticity and valorization of Mediterranean traditional products” (ARIMNET 2 call 2016) that aimed to provide reliable technological tools for authentication and quality assessment and make these tools widely available to stakeholders and consumers and promote traditional knowledge and the sustainable development of local economies [ 11 ].…”
mentioning
confidence: 99%
“…The study performed on cosmetic argan oil shows the feasibility of implementing authenticity criteria for argan oils by including limit values for trans-fatty acids and the ability to discern provenance using fatty acid profiling [ 8 ]. The research performed on truffles indicated that elemental and stable isotope composition together with multivariate statistical analysis classified truffles according to species and geographical origin [ 10 ]. Cross-validation resulted in a 74% correct classification rate for determining the species and a 77% correct classification rate for geographical origin discrimination.…”
mentioning
confidence: 99%
See 2 more Smart Citations